AB0825 Serum relaxin role and its importance in systemic sclerosis patients. (23rd January 2014) - Helmy, M.; Abdel Atty, E.; Saied, E.A.G.; Azab, N.
Abstract : Background: Systemic Sclerosis (SSc) is a connective tissue disorder characterized by fibrosis of the skin and may include the heart, lungs, kidneys, and gastrointestinal tract. Relaxin, a peptide hormone of the insulin superfamily, is involved in the promotion of extracellular matrix remodeling Objectives: This work aimed to measure serum relaxin, to study its antifibrotic, vasodilator, and proangiogenic effects and its association with disease activity in SSc patients (pts). Methods: This study included 40 pts with SSc, presenting in the outpatient clinic of rheumatology in Alexandria University Main Hospital, who met ACR Criteria for the classification of SSc, and 20 age-matched healthy persons as a control group. All pts were subjected to: Full medical history with particular stress on the duration of the disease, presence of Raynaud's disease, finger tip ulcers, renal, heart, and lung affection, Modified Rodnan Skin Score (M.R.S.S.) using ultrasound (U/S), 2D-Echocardiography to measure systolic pulmonary arterial pressure (sPAP), computerized tomography (CT) of both lungs, renal function tests, measurement of Serum Relaxin and serum vascular endothelial growth factor (sVEGF) using ELISA technique. Results: The level of sPAP, sVEGF, serum relaxin and urinary protein to creatinine ratio of the pts with SSc was significantly higher than controls (P=0.0001). There was no significant difference between pts with and without finger ulcers and interstitial pulmonary fibrosis (IPF) with regard to sPAP, skin thickness score and protein to creatinine ratio. Level of sVEGF of the pts with finger ulcers and IPF was significantly higher than pts without finger ulcers and/or IPF (P=0.0001). Pts with finger ulcers and IPF had significantly lower serum level of relaxin than pts without finger ulcers and/or IPF (P=0.0001). There was a strong positive correlation between (M.R.S.S.), both serum relaxin and sVEGF. Also, there was no correlation between serum relaxin and sVEGF. There was a positive correlation between sVEGF and sPAP of the pts with SSc but it didn't reach significant value (r=+0.27, P=0.06). Conclusions: Serum relaxin can be considered as a biomarker in SSc which correlates with disease activity and severity. Relaxin has emerged as a natural suppressor of age-related fibrosis in a number of tissues, including the skin, lung, kidney, and heart. Furthermore, relaxin has shown efficacy in the prevention and treatment of fibrosis due to SSc. References: Medsger TA, Steen V. Classification prognosis. In: Clements PJ, Furst DE. Systemic sclerosis. Baltimore: Williams & Wilkins; 1996: 51-64. Sherwood OD. Relaxin's physiological roles and other diverse actions. Endocr Rev 2004; 25:205-34. Clements P, Lachenbruch P, Seibold J, et al. Inter and intraobserver variability of total skin thickness score (Modified Rodnan Skin Score) (MRSS) in systemic sclerosis. J Rhumatol 1995; 22:1281-5. Disclosure of Interest: M. Helmy Consultant for: Rheumatology, E. Abdel Atty Consultant for: Hepatology, E. Saied Consultant for: Rheumatology, N. Azab Consultant for: Chest